Conceptual framework for a sui generis trade agreement that serves ACP needs in the 21st century : final report - Stevens, Christopher (Institute of Development Studies [S.l.], 2000)
Proposes that the ACP consider replacing the 'single-document format' of the Lomé Convention with a family of agreements.